2018
DOI: 10.1002/cnma.201800089
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Graphene Oxide and Graphene: From Imagination to Industrialization

Abstract: During the past 32years, more than 103000 research articles with term graphene in the title or in manuscript have been recorded in the Scopus database. This exceptional reputation of graphene is due to numerous reasons; the most significant one appears to be its incomparable physical properties, resulting in real-time application in many fields of science and technology. That's why it seems to be absolutely justified that "graphene possesses everything's what you want". This article is a tribute to the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 131 publications
0
45
0
Order By: Relevance
“…Graphene, discovered by Geim and Novoselov in 2004, is relatively a new two dimensional (2D) sheet-like material in which a honeycomb or hexagonal structure with a flat lattice configuration, completely composed of sp 2 hybridized carbon atoms that are covalently bound, is densely packed [102,103]. Graphene, an atomic layer of graphite, is the unique carbon's allotrope, where each atom is tightly linked to its neighbors by an only electronic cloud in which a C-C bond distance is 0.142 nm [104]. It is considered as a fundamental basis for all carbon allotropes and as the mother of a graphitic family for all the dimensions.…”
Section: Nomenclature and Fundamental Aspectsmentioning
confidence: 99%
“…Graphene, discovered by Geim and Novoselov in 2004, is relatively a new two dimensional (2D) sheet-like material in which a honeycomb or hexagonal structure with a flat lattice configuration, completely composed of sp 2 hybridized carbon atoms that are covalently bound, is densely packed [102,103]. Graphene, an atomic layer of graphite, is the unique carbon's allotrope, where each atom is tightly linked to its neighbors by an only electronic cloud in which a C-C bond distance is 0.142 nm [104]. It is considered as a fundamental basis for all carbon allotropes and as the mother of a graphitic family for all the dimensions.…”
Section: Nomenclature and Fundamental Aspectsmentioning
confidence: 99%
“…[13] In recent years, graphene/ manganese dioxide composite electrode materials have be-come a hot point for seeking superior supercapacitive performance. [14][15][16][17] Graphene, a hexagonal honeycomb lattice composed of sp 2 hybrid carbon atoms, [18] is a new but very competitive candidate for electroactive carbon electrode material, [19] due to its excellent electrical conductivity, [20,21] mechanical strength [22] and specific surface area. [23] So far, the fruitful scientific research results have confirmed its potential application as electrode materials in solar cells, [24] secondary batteries, [25] and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Since, graphene was discovered in 2004, it becomes most popular for human civilization' thus, it is one of the most wonderful achievements of science and technology [1]. Graphene is one of the high stable materials, because of very close or tight packing of atoms in the crystal lattice of graphene and its related materials [2,3]. Due to enormous reputation of graphene, large research communities, had given significant attention to design and development of graphene materials for varies industrial applications like longer-lasting batteries, efficient solar cells, corrosion prevention, circuit boards, display panels, medical purposes, [4] etc.…”
Section: Introductionmentioning
confidence: 99%